Interactive Learning Methods for Enhancing Students’ English Skills at SMA Negeri 14 Palembang - Juliantina; Muhammad Aditya Purnomo; Nurul Aulia (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to investigate the implementation of interactive learning methods for enhancing students’ English skills at SMA Negeri 14 Palembang. The research focuses on identifying how interactive activities improve students’ speaking, listening, reading, and writing abilities as well as their motivation and classroom participation. This study employed a qualitative descriptive method. The participants consisted of English teachers and students of SMA Negeri 14 Palembang. The instruments used in this research were classroom observations, interviews, and documentation. Data were collected through direct observation of teaching-learning activities, semi-structured interviews with teachers and students, and analysis of learning documents. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that interactive learning methods such as group discussions, role plays, educational games, collaborative learning, and technology-based activities significantly enhanced students’ English skills and increased their confidence in using English during classroom interaction. The study also found that interactive learning created a more enjoyable and motivating learning atmosphere. In conclusion, interactive learning methods are effective in improving students’ English proficiency, participation, and motivation in English language learning at SMA Negeri 14 Palembang.